Corporate Governance and Business Resilience in the Banking Industry - Friday Ogbu, Edeh; Evelyn Dania, Ndidi; Collins Okechukwu, Irem; Dayo Benedict, Olanipekun; Namono, Rehema; Omweno Nyameyio, Enock; Hamidah, Nabawanuka (INTI International University, 2024)
The unstable banking business environment and ethical questions that bedeviled the industry have opened new windows for researchers and policymakers on how best to tackle the menace. But as researchers keep pace on how best banking institutions can remain unperturbed with preparation for future adversities and bearing in mind the shareholders' wealth, the concept of resilience becomes the beacon of hope for managers and directors alike. 139 participants drawn from ten interest-deposit money banks in south-eastern Nigeria were selected for this inquiry. The result of this study demonstrated that corporate governance predicted business resilience positively. It was concluded that corporate governance that is predicated on board independence, board size, board effectiveness, leadership quality, and accountability would strengthen the resilience of interest deposit money banks. This study recommends that managing directors of interest deposit money can leverage corporate governance measures utilized in this study to strengthen the resilience capability of their organisations.